2016
DOI: 10.3329/jbau.v12i2.28702
|View full text |Cite
|
Sign up to set email alerts
|

Studies on public health and hygiene condition of retailers at fish markets in south-central Bangladesh

Abstract: Bangladesh is a fish producing country from the ancient history due to its deltaic nature agro-ecologically. Accordingly fish marketing systems developed in traditional systems sincelong. This study was conducted in two retail fish markets located in Rajbari and Barisal Sadar Upazila in the south central region of Bangladesh focusing public health and hygiene condition of retailers. The questionnaire interview with 30 retailers and participatory rural appraisal (PRA) tools were used to get the information from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 8 publications
1
8
0
Order By: Relevance
“…Despite their low literacy level, these women fish vendors have learned fish cutting, processing, and price negotiation techniques through ancestral rituals passed down from generation to generation. Infrastructural facilities, particularly fish landing centers, and wholesale and retail markets, were inadequate and unsanitary, posing serious threats to public health on a regular basis (Alam et al, 2016) [20]. In terms of hygiene, we discovered that the situation at Bazaar Samiti was the worst because there was no adequate supply of water, no dumping site for fish residue, an inadequate drainage system, and freely roaming stray dogs.…”
Section: Fig 4 Age Group Of Women Fish Vendorsmentioning
confidence: 92%
See 1 more Smart Citation
“…Despite their low literacy level, these women fish vendors have learned fish cutting, processing, and price negotiation techniques through ancestral rituals passed down from generation to generation. Infrastructural facilities, particularly fish landing centers, and wholesale and retail markets, were inadequate and unsanitary, posing serious threats to public health on a regular basis (Alam et al, 2016) [20]. In terms of hygiene, we discovered that the situation at Bazaar Samiti was the worst because there was no adequate supply of water, no dumping site for fish residue, an inadequate drainage system, and freely roaming stray dogs.…”
Section: Fig 4 Age Group Of Women Fish Vendorsmentioning
confidence: 92%
“…Literacy level is critical for effective participation and operational skill in all income-generating activities. It was assumed that the education of fish retailers would help them gain better access to relevant technical information [20]. In this study, it was discovered that only a few of the male fishermen are literate, with only a high school education.…”
Section: Fig 4 Age Group Of Women Fish Vendorsmentioning
confidence: 94%
“…Among the samples collected about 68.8% and 21.52% isolates were E. coli positive. Alam et al, (2014) conducted study in two retail fish markets located in Rajbari and Barisal Sadar Upazila in the south central region of Bangladesh focusing public health and hygiene condition of retailers and indicated that due to poor infrastructural facilities, poor washing facilities, landing, handling, distribution, marketing and quality assurance, the baskets were contaminated by pathogenic bacteria.…”
Section: Basket Samplesmentioning
confidence: 99%
“…Akinjogunla et al [13] identified stream as a source of contamination to fish products. Stream is a popular water source for processing fish as revealed by Alam et al [21] who confirmed that about half of fish mongers in Bangladesh used stream water to process their fish. Majority (68.2%) of the respondents in this study reported that they washed their hands at the end of the day, 38.6% said they carried out hand-washing after using the toilet, 34.1% stated that they washed their hands before handling fish while 34.1% revealed that they washed their hands after handling fish.…”
Section: Sources Of Water Supply and Hygiene Practicesmentioning
confidence: 99%